(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract The background of this thesis writing is the rampant divorce of wives from their husbands in the Class IA Makassar Religious Court. In general, divorce occurs because the husband is not responsible for it. Marriage is a word / term that is heard almost every day in conversations or in print or digital / electronic mass media. Marriage contains sacred values, so its implementation includes the preparation stage for the implementation of the marriage ceremony and the stage of the continuation of marriage. Both parties must always carry out their religious values ​​in accordance with the religion and beliefs they believe. Divorce This claim is a divorce caused by a prior lawsuit by one of the parties to the Court and by a Court decision. The reasons referred to, are stated in the explanation of Article 39 paragraph 2 of the Marriage Law and are repeated in Article 19 of the Verstek Implementation Regulations contained in Article 125 HIR that the defendant never came to appear and did not order another person as his representative or proxy to come before him. despite the fact that the defendant has been formally summoned, and it is proper that it is not evident that the defendant's absence was due to a valid obstacle, then based on article 149 (1) R.Bg. Abstrak Penulisan skripsi ini dilatarbelakangi maraknya cerai gugat istri kepada suami di Pengadilan Agama Makassar Kelas IA. Pada umumnya perceraian terjadi karena tidak adanya tanggung jawab suami. Perkawinan merupakan suatu kata/istilah yang hampir tiap hari didengar dalam pembicaraan atau dalam media massa cetak maupun digital/elektronik.Perkawinan mengandung nilai sakral, maka dalam pelaksanaannya meliputi tahap persiapan pelaksanaan upacara perkawinan dan tahap kelanjutan perkawinan. Kedua belah pihak harus senantiasa melaksanakan nilai-nilai religiusnya sesuai dengan agama dan kepercayaan yang diyakininya. Cerai Gugat ini adalah perceraian yang disebabkan oleh adanya suatu gugatan lebih dahulu oleh salah satu pihak kepada Pengadilan dan dengan suatu putusan Pengadilan. Alasan yang dimaksud, tercantum dalam penjelasan Pasal 39 ayat 2 Undang-Undang Perkawinan dan diulang lagi sama bunyinya dalam Pasal 19 Peraturan Pelaksanaan Verstek terdapat pada Pasal 125 HIR bahwa tergugat tidak pernah datang menghadap dan tidak menyuruh orang lain sebagai wakil atau kuasanya untuk datang menghadap di persidangan meskipun tergugat telah dipanggil secara resmi, dan patut sedang tidak ternyata bahwa ketidak- hadiran tergugat tersebut disebabkan oleh suatu halangan yang sah, maka berdasarkan pasal 149 (1) R.Bg.